Learning independence and teacher teaching skills: Does it affect learning outcomes when face-to-face learning is limited - Apri Nuryanto; Rizki Ramadani (Jurnal Pendidikan Vokasi, 2022)
Limited face-to-face learning is a learning policy implemented by schools to prevent coronavirus transmission during the pandemic. Amidstface-to-face learning has become limited, so that it requires students to study more independently from home. Teachers are also required to maximize class time and are also required to be skilled in providing learning outside of student learning hours in class. This study aims to determine (1) the influence of student learning independence on learning outcomes, (2) the influence of teachers' teaching skills on learning outcomes, and (3) the influence of student learning independence and teacher teaching skills during limited face-to-face learning on student learning outcomes. The research method used is quantitative with a correlational approach. This research was conducted at SMK throughout Sleman Regency. Respondents were 26 schools with a total of 2209 students. The sample calculation used Slovin with 339 samples. Data collection using questionnaires and tests with the help of google forms. The data obtained were then analyzed with several techniques such as description analysis; normality, homogeneity, multicollinearity tests; and hypothesis tests consisting of simple regression tests and multiple regression tests. The study's results obtained 1.) Learning outcomes were positively and significantly influenced by student learning independence with a value of sig. 0.023 < 0.05; 2.) Learning outcomes are positively and significantly influenced by the teaching skills of teachers with sig grades. 0.000 < 0.05; and 3.) Learning outcomes are also positively and significantly influenced by student learning independence and teacher teaching skills with a value of sig. 0.000 < 0.05.